Improving Microstructures of Concrete Using Ca(C18H35O2)2. (2015) - Maryoto, Agus
Abstract: Most of the water used in the concrete evaporates after the concrete hardens. Due to this processes, there are millions of capillaries in the hardened concrete. Consequently, concrete is a porous material. The liquids and gases enter into the concrete through the capillaries. Penetrability of the fluids into the concrete can be reduced using some methods. One of them is using additives which increase hydrophobic property of concrete. Hydrophobic action in the concrete can be achieved by adding stearic acid. This study tries to investigate effect of Ca (C18 H35 O2 )2 (calcium stearate) in the microstructures of the concrete. Five contents of calcium stearate is utilized which are 0, 1, 2, 3, and 4 kg in one cubic meter of concrete mix. Three testing model which are compressive stress test, permeability test and macro cell corrosion test, are conducted in order to study the effect of calcium stearate in the concrete. Each testing model consists of 15 specimens. Cylinder with 150 mm diameter and 300 mm height, cube 150 mm x 150 mm x 150 mm and beam with 280 mm length, 224 mm width and 152 mm height are tested for compressive stress, permeability and macro cell corrosion respectively. The results show that usage of calcium stearate tend to increase compressive stress of concrete until the content of calcium stearate is 4 kg, but the increasing is insignificant. Concrete with 3 kg of calcium stearate produces the minimum value of permeability and macro cell corrosion. Based on the result, it can be concluded that calcium stearate improves microstructures of concrete.